Sanction Against Notary in Authentic Deed Malpractice - Asyril Rizky Akbar; Tarring, Anisah Daeng (Alauddin Law Development Journal (ALDEV), 2024)
The notary profession has a responsibility to the community and must comply with the Notary Position Law and the Notary Code of Ethics. A Notary is also a human being who is not free from mistakes in making authentic deeds. These malpractices can sometimes be realized and can also be unconscious, especially in making the authentic deed. There has been no update regarding the UUJN but there are many forms of notarial errors. Therefore, this study raises the forms of notary consequences that must be accepted by him if there is malpractice in making authentic deeds. This research is a normative research, using legislative and conceptual approaches, obtaining secondary data with literature studies which are then analyzed with descriptive qualitative. The results of this study indicate that the application of both civil sanctions, administrative sanctions, and code of ethics sanctions. Because it is proven to commit an offense.